PENERAPAN SIAGA SEHAT MOBILE KIT DAN INSTALASI TEKNOLOGI AIR BERSIH DALAM PENANGGULANGAN KESEHATAN PASCA BENCANA BANJIR BANDANG - Dwi Apriadi; Dwi Novilolita; Debby Ratno Kustanto; Masyithah Fadhani; Vistaria Furkano; Junios Junios; Dwi Mutia Wenny (Institut Kesehatan Yarsi Mataram, 2026)
Background: The flash floods (galodo) that occurred in South Batipuh District and X Koto District, Tanah Datar Regency, West Sumatra, had significant impacts on public health, health service systems, access to clean water, as well as sanitation and environmental conditions. Damage to infrastructure, disruption of health service access, and environmental degradation increased the risk of infectious and environmentally related diseases and exacerbated pre-existing non-communicable diseases among affected populations. Purpose: This Community Service Program aimed to describe and analyze the implementation of the Siaga Sehat Mobile Kit, the installation of clean water and sanitation technologies, and the safety environment for recovery approach as post-disaster health recovery interventions. Method: A participatory descriptive approach was employed through mobile health services, installation of emergency clean water facilities, distribution of hygiene supplies, health education, and capacity building for community health centers (puskesmas) and local communities. The activities were conducted from 19 to 21 December 2025 in several affected villages (nagari), involving lecturers from Universitas Prima Nusantara Bukittinggi, primary health care personnel, volunteers, and local government authorities. Results: The results demonstrated improved access to basic health services for vulnerable groups, enhanced availability and quality of clean water, and strengthened partner capacity in post-disaster health and sanitation management. Conclusion: The program contributed to strengthening the resilience of the local health system and shows potential for replication in other disaster-prone areas.